PENERIMAAN OPINI AUDIT GOING CONCERN PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Siswi Istining Tyas & Kun Ismawati (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2019)
This study aims to determine the effect of profitability, company growth, previous year’s audit opinion, company size, and Debt to Asset Ratio to acceptance of going concern audit opinion. This type of research is an empirical research, and the study was conducted at the manufacturing companies listed in Indonesia Stock Exchange in 2011 until 2013. The sampling technique used purposive sampling method with a total sample of 31 companies and 93 observations. Analysis techniquues used in this research is descriptive analysis and logistic regression analysis. The results show that profitability does not significantly influence on acceptance of going concern audit opinion on manufacturing companies in the Indonesia Stock Exchange, Company Growth significantly and negatively related to acceptance of going concern audit opinion on manufacturing companies in the Indonesia Stock Exchange, Previous year’s audit opinion has positive effect significantly related to acceptance of going concern audit opinion on manufacturing companies in the Indonesia Stock Exchange, company size does not significantly influence the timeliness of financial reports on manufacturing companies in the Indonesia Stock Exchange and debt to asset ratio has positive effect significantly related to acceptance of going concern audit opinion on manufacturing companies in Indonesia Stock Exchange.Keywords: Profitability, Company Growth, Previous year’s audit opinion, Company Size, Debt to Asset Ratio, Acceptance of Gooing Concern Audit Opinion.